2014
DOI: 10.1590/1678-4499.0150
|View full text |Cite
|
Sign up to set email alerts
|

Componentes de produção e morfologia de raízes de mandioca sob diferentes preparos do solo

Abstract: ResumoCom o objetivo de avaliar o efeito de cultivo mínimo, plantio convencional e plantio direto sobre os componentes de produção e a morfologia das raízes tuberosas de mandioca da cultivar de mesa IAC 576-70, conduziu-se este experimento a campo em delineamento experimental de blocos ao acaso, com parcelas subdivididas com seis repetições. Os preparos do solo, cultivo mínimo, preparo convencional e plantio direto, foram consideradas as parcelas e as épocas de avaliação, em dias após o plantio, foram consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
2
10
0
3
Order By: Relevance
“…In our study, the water content in the upper soil layers in NT and the high penetration resistance might have induced the superficial development of fibrous roots, at the root system formation phase. This hypothesis can be supported by the earlier falling of the leaves, observed under this treatment at 180 DAP, which may be related to the difference observed in root DM at 210 DAP, and in the other yield components of cassava such as fresh matter and root diameter, as reported by Figueiredo et al (2014).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In our study, the water content in the upper soil layers in NT and the high penetration resistance might have induced the superficial development of fibrous roots, at the root system formation phase. This hypothesis can be supported by the earlier falling of the leaves, observed under this treatment at 180 DAP, which may be related to the difference observed in root DM at 210 DAP, and in the other yield components of cassava such as fresh matter and root diameter, as reported by Figueiredo et al (2014).…”
Section: Discussionsupporting
confidence: 71%
“…The decrease of DM in the tuberous root of those plants under NT was associated with neither tuberous root morphology nor anatomy, as demonstrated by Figueiredo et al (2014) and Figueiredo et al (2015). However, it can be associated with the morphology and physiology of the fibrous roots as affected by porosity and soil resistance penetration, as shown by Hernandez-Ramirez et al (2014).…”
Section: Discussionmentioning
confidence: 93%
“…Root growth continued up to 329 DAE, close to the period established by Conceição (1981), from 6 to 10 months. The average length of 69.2 cm was greater than that reported in the literature Albuquerque et al, 2009;Albuquerque et al, 2012;Figueiredo et al, 2014). This can be attributed to the characteristics of the cultivar, which, due to its smaller diameter, makes up for lower tuberisation by increasing length.…”
Section: Resultsmentioning
confidence: 62%
“…Usually, the number and length of roots do not constitute production components limiting to yield in cassava, as they can be offset by a growth in diameter. Figueiredo et al (2014) found a close positive correlation between root fresh matter and root diameter, whereas the number of roots explained only 60 % in the IAC 576-70 cultivar.…”
Section: Resultsmentioning
confidence: 86%
“…Esse fato limita consideravelmente a capacidade de produção do pequeno produtor, que tem como única alternativa efetuar o plantio de forma manual. Para Figueiredo et al (2014), é importante que se desenvolvam modelos de plantio de mandioca em sistemas conservacionistas, pois o preparo convencional do solo promove a erosão laminar e perdas de solo. O sistema de plantio direto na palha se mostra como uma alternativa viável à produção de mandioca no Brasil.…”
Section: Introductionunclassified